Pre-treatment integrase inhibitor resistance is uncommon in antiretroviral therapy-naive individuals with HIV-1 subtype A1 and D infections in Uganda. (1st June 2021) - McCluskey, Suzanne M.; Kamelian, Kimia; Musinguzi, Nicholas; Kigozi, Simone; Boum, Yap; Bwana, Mwebesa B.; Muzoora, Conrad; Brumme, Zabrina L.; Carrington, Mary; Carlson, Jonathan; Foley, Brian; Hunt, Peter W.; et al.
Abstract : Objective: Dolutegravir (DTG) is now a preferred component of first-line antiretroviral therapy (ART). However, prevalence data on natural resistance to integrase inhibitors [integrase strand transfer inhibitors (INSTIs)] in circulating non-subtype B HIV-1 in sub-Saharan Africa is scarce. Our objective is to report prevalence of pre-treatment integrase polymorphisms associated with resistance to INSTIs in an ART-naive cohort with diverse HIV-1 subtypes. Design: We retrospectively examined HIV-1 integrase sequences from Uganda. Methods: Plasma samples were derived from the Uganda AIDS Rural Treatment Outcomes (UARTO) cohort, reflecting enrollment from 2002 to 2010, prior to initiation of ART. HIV-1 integrase was amplified using nested-PCR and Sanger-sequenced (HXB2 4230-5093). Stanford HIVdb v8.8 was used to infer clinically significant INSTI-associated mutations. Human leukocyte antigen (HLA) typing was performed for all study participants. Results: Plasma samples from 511 ART-naive individuals (subtype: 48% A1, 39% D) yielded HIV-1 integrase genotyping results. Six out of 511 participants (1.2%) had any major INSTI-associated mutations. Of these, two had E138T (subtype A1), three had E138E/K (subtype D), and one had T66T/I (subtype D). No participants had mutations traditionally associated with high levels of INSTI resistance. HLA genotypes A*02:01/05/14, B*44:15, and C*04:07 predicted the presence of L74I, a mutation recently observed in association with long-acting INSTI cabotegravir virologic failure. Conclusion: We detected no HIV-1 polymorphisms associated with high levels of DTG resistance in Uganda in the pre-DTG era. Our results support widespread implementation of DTG but careful monitoring of patients on INSTI with virologic failure is warranted to determine if unique mutations predict failure for non-B subtypes of HIV-1.